El feminicidio en la televisión de señal abierta de Lima - García Toledo, María Magdalena (2016)
This research is the continuation of two studies carried out at the Institute of Humanistic Research of the National Universidad of San Marcos during the years 2011 and 2012. In the first case, the subject matter of study was “Violence, Women and Television”; in the second case, it was “Violence, Women and Print Media”.However, the subject matter under this study is more specific since previous research dealt with general violence against women, whereas this study deals particularly with the “femici- de”. This phenomenon defines specific violence against women on account of being female, which precludes women from enjoying their inherent social and personal rights as human being. These crimes are part of the “machismo”, understood as a collective behavior where power is unevenly exercised in favor of men. It is considered a worldwide pandemic and a cause for concern of governments, legal, social, economic and educational systems.Unfortunately, this phenomenon has been increasing more and more in our country; and the mass media, particularly the television, have been reporting on this in an insufficient, biased and wrong way. Eventually, this makes things remain unchanged and prevents the issue from being tackled in a better way to eradicate violence.This study will analyze a sample of free-to-air television news to detect the positive and negati- ve aspects mentioned above and determine whether the television is fulfilling its correspon- ding social, informative and truthful labor.